Functional Traits and Phylogenetic Effects Drive Germination of Lemur‐Passed Seeds - Camille M. M. DeSisto; Zico Zandry; Telesy Feno; Borna Zareiesafandabadi; Jean Randrianasy; Jean Tiamanana; Dominique Randrianasolo; Manadina Rasolofo; George Raveloson; Franclin Zerimanana; Onja Razafindratsima; James P. Herrera; et al. (Ecology and Evolution, 2025)
ABSTRACT Frugivore‐mediated seed dispersal drives ecological functioning across tropical forests. The biological mechanisms affecting seed dispersal outcomes, as well as the role of specific functional traits in plants and their dispersers, is still not well understood. To address this gap, we conducted germination experiments in eight species of captive and two species of wild lemurs, which disperse different plant species. We (1) quantified the effects of pulp removal, seed priming, and feces effects (nutrient/microbial fertilization) through gut passage as mechanisms, (2) determined the effect of frugivore species on germination, and (3) assessed how individual plant and animal traits affected two seed germination outcomes: success rates and time‐to‐germination. Accounting for phylogenetic non‐independence of plants and estimating phylogenetic signal, we evaluated the effects of lemur gut passage and functional traits in a Bayesian framework. Seed priming during gut passage was the primary mechanism through which lemurs improved germination rates and decreased time‐to‐germination. Gut passage influenced the effect of seed length on germination probability but not time‐to germination. Germination outcomes varied by disperser species and seed size. Furthermore, seeds passed by male lemurs were 40% more likely to germinate than those passed by female lemurs. Germination probability was more similar for closely related plant species compared to those that were more distantly related, while the plant phylogenetic effects on time‐to‐germination were weaker. Moreover, germination depended on experimental setting; for example, lemur gut passage decreased time‐to‐germination in captive, but not wild settings. Our results highlight the complexity of biological mechanisms determining seed dispersal outcomes; ecological and evolutionary factors were important drivers of germination. Considering a diversity of potential effects is critical for advancing a mechanistic understanding of species interactions and their outcomes.